2017
DOI: 10.1039/c7gc01166k
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free Suzuki–Miyaura coupling using ruthenium(0) nanoparticles and a continuously irradiating microwave system

Abstract: A good combination between a continuously irradiating microwave system and recyclable Ru(0) nanoparticle for ligand-free Suzuki–Miyaura coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…While supported Pd catalysts catalyzed the coupling reactions at relatively higher reaction temperature, with more palladium content and prolonged reaction time, which makes the process less efficient. Recently, supported Ru NPs were also investigated for ligand‐free Suzuki‐Miyaura coupling using dimethoxyethane at 80 °C, under microwave irradiation . Borkowski et al.…”
Section: Introductionmentioning
confidence: 99%
“…While supported Pd catalysts catalyzed the coupling reactions at relatively higher reaction temperature, with more palladium content and prolonged reaction time, which makes the process less efficient. Recently, supported Ru NPs were also investigated for ligand‐free Suzuki‐Miyaura coupling using dimethoxyethane at 80 °C, under microwave irradiation . Borkowski et al.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its low leaching, our newly developed SGlPd catalyst could also be recycled up to 10 times without any discernible decrease in its catalytic activity. Nickel (SANi(0)) 24) After we obtained the above results, we decided that the in situ PSSO method could be used to immobilize various transition-metal NPs, including base metals. Our in situ PSSO method can be used easily to produce Ni NPs with low Ni leaching and good recyclability for use in organic synthesis.…”
Section: Liquid-phase Combinatorial Experimentsmentioning
confidence: 99%
“…23) Transmission electron microscopy (TEM) analyses and extended X-ray absorption fine structure (EXAFS) experiments were performed to clarify the geometrical properties of Pd catalysis in SAPd(0). X-ray absorption near-edge structure (XANES) analysis 24) at S and C K-edge were used to determine the chemical states of sulfur and carbon in SAPd(0). As a consequence, we found that SAPd(0) has approximately ten layers of self-assembled Pd(0) NPs, a size of less than 5 nm, on Au surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of nano—catalysts is proved by their frequent applications in various transformations like oxygen reduction, water oxidation, oxidation of cyclohexenone to phenol, hydrogen generation from formic acid, ultrafast coupling of aryllithium reagents with aryl bromides, Se–Se bond activation, C–O bond activation, one–pot conversion of nitro phenol to benzoxazole, CuAAc reactions, Suzuki–Miyaura coupling, alkyne–cis–semihydrogenation, A 3 –coupling, peptide bond formation, acceptorless dehydrogenative aromatization, selective alcohol oxidation, aerobic oxidation of diaryl and aryl(hetero) methylenes,and C–H bond activation. In spite of these valuable catalytic properties of nanoparticles, there is a significant amount of research is needed to develop methods using economic, cost–effective and readily available non–noble metal nano catalysts.…”
Section: Introductionmentioning
confidence: 99%